Prevalence of Erectile Dysfunction and its associated factors among men in government health clinics in Kuantan: Preliminary report - Wan Mahmod, Wan Fatimah Suriyani; Che' Man, Mohamad; Yusof, Muhammad Zubir; Che Alhadi, Shahidah; Ab Rashid, Islah Munjih; Osman, Iskandar Firzada (IIUM Press, 2022)
Erectile dysfunction (ED) is a significant issue that should not be overlooked in the clinic. The purpose of this study was to determine the prevalence of ED and its associated factors among men who visited a government health clinic in Kuantan, Pahang, Malaysia. A total of 171 men aged 18-60 years participated in this cross-sectional study. Data of demographic, medical history and lifestyle were gathered through self-administered questionnaire. A validated Malay version International Index of Erectile Function (IIEF-5) was used to assess ED. The overall prevalence of self-reported ED was 71.9%. The prevalence of ED according to severity was as follow mild (43.9%), mild to moderate (25.7%), moderate (1.8%) and severe (0.6%). Multivariate analysis showed that ED associated with unhealthy status (odds ratio [OR 5.490, 95% confidence interval [CI] 2.184-13.795) and age of patient (OR 1.059, 95% CI 1.013 -1.106). ED has significant prevalence among adult male healthcare clinic attendees in Kuantan. Person health status and age were significant associated with ED.